2017
DOI: 10.1001/jama.2017.7092
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Weight Gain From Early to Middle Adulthood With Major Health Outcomes Later in Life

Abstract: In these cohorts of health professionals, weight gain during adulthood was associated with significantly increased risk of major chronic diseases and decreased odds of healthy aging. These findings may help counsel patients regarding the risks of weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
353
2
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(377 citation statements)
references
References 34 publications
19
353
2
3
Order By: Relevance
“…33 A study from the USA reported that each 5-kg increase in bodyweight during early and middle adulthood was associated with a 30% increased risk of type 2 diabetes and a 14% increased risk of hypertension. 34 Thus, the potential significance of the effect of Atole on fatness, especially abdominal fatness, should not be understated.…”
Section: Discussionmentioning
confidence: 99%
“…33 A study from the USA reported that each 5-kg increase in bodyweight during early and middle adulthood was associated with a 30% increased risk of type 2 diabetes and a 14% increased risk of hypertension. 34 Thus, the potential significance of the effect of Atole on fatness, especially abdominal fatness, should not be understated.…”
Section: Discussionmentioning
confidence: 99%
“…Insurance companies may need to evaluate their approaches to coverage accordingly. Prevention is key as noted from two long-term cohort studies which found that “weight gain from early to middle adulthood was associated with increased risk of morbidity and mortality, and decreased odds of achieving the composite healthy aging outcome among women and men…weight gain as little as 5 kg was associated with significantly elevated incidence of a composite measure of major chronic diseases, consisting of type 2 diabetes, cardiovascular disease, cancer, and nontraumatic death.” 122 …”
Section: Resultsmentioning
confidence: 99%
“…1 An 18-year follow-up of almost 93 000 women in the Nurses’ Health Study revealed a dose-response association of weight gain and obesity with several cancers. 2 …”
mentioning
confidence: 99%
“…Furthermore, the sequelae of these diseases are related to the severity of obesity in a dose-response fashion. 2 It is therefore not surprising that obesity accounts for a significant portion of health care costs.…”
mentioning
confidence: 99%